PARENTING EFFICACY OF PARENTS FOR CHILDREN WITH VISUAL IMPAIRMENT: A LITERATURE REVIEW - Raiza Aulia (Psikoislamedia : Jurnal Psikologi, 2020)
The gift of God in establishing a household is the presence of a child. Caring for children is an important concern for parents, especially children who have special needs. Parents who have children with special needs with visual impairment become a big challenge and generally parents will experience stress, anxiety and depression in caring for children with visual impairment. The success of parenting in children with visual impairment must be in accordance with its limitations so that children can reach the aspects given in accordance with learning blindness. Parents also have confidence in success in caring for children with visual impairments so that their children have the same abilities as normal children. This research is interesting because in the literature used there are results that parenting efficacy in parents with children with visual impairment varies, namely building self-confidence, developing social mobility and skills and emotional support, appreciation, and informative.